Gambaran Kesiapsiagaan Pedagang Pasar dalam Penanggulangan Bencana Kebakaran di Pasar Legi Kota Blitar (Disaster Nursing Research) - Agus Khoirul Anam; Sri Winarni (STIKes Patria Husada Blitar, 2016)
Indonesia has a lot of potential natural and non-natural disasters. Non-natural disasters which often happened are fire disasters. One of them was market fire. In January 2015 until April 2015, there was an increasing more than 50 on fire in bigger traditional market and 90 smaller traditional market in all over indonesia. The purpose of this research was to describe the marketeer preparedness of fire disaster management of Legi market Blitar city. The research method used descriptive design. The population in this research was a marketeer Legi Kota Blitar about 584 marketeer and the sample was 58 marketeer taken by purposive sampling technique. The data collection was conducted by questionnaire. The results showed that the lack of preparedness of marketeer in the fire disaster still less as much as 60.3% (35 marketeer). It was caused by there was no information of manner about the preparedness of fire disaster, no training, didn’t have the telephone number of fire department, no simple fire extinguishers, could not use a fire APAR or hydrant, and unable to perform first aid to fire victims. Recomendation of BPBD departement necessary gave education and training about fire disaster preparedness, especially in the market so it could decrease the risk of fire disaster in Legi market Blitar city.